Desenvolvimento de β-dicetonas e estudo das propriedades luminescentes de complexos com íons lantanideos - Batista, Poliane Karenine (2011)
The lanthanide complexes have been extensively applied in several fields of knowledge. Most of these applications depend on the catalytic and spectroscopic properties of trivalent lanthanide ions. In this context, this work involves the synthesis of two classes of two-functionalized ligands between bases of nitrogen and β-diketones (classes A and B) order at future applications as catalysts for organic reactions and / or chemical sensors. The Class A, β-diketone linked to bidentate nitrogen ligands such as 2,2 -bipyridine and 1,10-phenanthroline were designed for this work, however no success was obtained in the last step of the synthesis. Three mixed β-diketones and pyridine ligands: 1,3-phenyl-(4-pyridyl)-propane-1,3 dione (12) (Class A), 1,3-methyl-2-(4-pyridyl)-propane-1 ,3-dione (16) and 1,3-diphenyl-2-(4-pyridyl)-propane-1 ,3-dione (17) (class B) were obtained with moderate yields. All synthesized intermediates and synthesized ligands were characterized by mass spectrometry, 1H and 13C NMR. The complex tris-β-diketonates of Eu3+ and Gd3+ were synthesized with the ligand 12. The ability of the ligand to donate energy to the lanthanide ions was evaluated by the luminescence spectra of the complex between 12 and Gd3+ ion, where it was observed that the ligand acts as "antenna" very efficient, sensitizing the luminescence of the metal center. From the complex of ligand 12 with the spectroscopic properties of Eu3+ complex formed were investigated based on data obtained from emission, excitation spectras and decay curves luminescence. From the emission spectra was possible to obtain a series of spectroscopic parameters for the complex of the Eu3+ ion where it was noticed the absence of the bands related to the fluorescence and / or phosphorescence of the ligand, suggesting that the processes of energy transfer from ligand to the excited levels of the metal center are very efficient.